Studies on the Synthesis of Novel Four-Membered Cyclic Oxaphosphetanes via Intramolecular Mitsunobu Reaction of Bishydroxyalkylphosphinic Acids - Kaboudin, Babak; Haghighat, Hamideh; Yokomatsu, Tsutomu (Synlett, 2016)
Studies on the synthesis of novel four-membered cyclic oxaphosphetanes from bishydroxyphosphinic acids is reported. Investigations showed that the conversion proceeds through an intramolecular Mitsunobu cyclisation of bishydroxyphosphinic acids with a mixture of triphenylphosphine and diisopropylazodicarboxylate (DIAD) in toluene–CH2Cl2 at room temperature. The treatment of two diastereomers of bishydroxymethylphosphinic acids (dl pair and meso) with a mixture of triphenylphosphine and DIAD gives only one stereoisomer of the cyclic oxaphosphetane.
Keywords: bishydroxyphosphinic acids; oxetanes; oxaphosphetane; cyclic phosphinic acids; Mitsunobu reaction